How Gross Domestic Product and Education Affect Health Expenditure in Malaysia - Low, Ai Vy (School of Social Sciences, 2015)
This paper attempts to identify the relationship between education and income distribution and its impact on health status of the individual in Malaysia. This research accounted Malaysia income and education level from the years of 1981-2011 based on the information provided by Malaysia Statistical Department and World Bank. Simple linear regression test is being used to analyse the findings. Health care is one of the most important in Malaysian life. There is an increasing awareness about health status among society in Malaysia. Most of the people there spend part of their income on health care which shown in our research income level is one of the main determinants of health status. Income level had a positive relationship with health status. The higher the income earned by the Malaysian, the more them aware their health status by seeking for a medical check-up. Apart from that, this research also emphasized on the education level as the other determinants of health status. Educated family seems like care about their health status.